(untitled) (Annals of Medical Research, 2021)
Aim: Survivin is an “inhibitor of apoptosis” protein. Survivin expression is a poor prognostic factor in a variety of solid tumors. In this clinicopathological study, we aimed to investigate survivin immunostaining of leiomyomas, leiomyoma variants, STUMP (Uterine smooth muscle tumor of uncertain malignant potential)’s and LMS (leiomyosarcoma). Our second objective was to investigate whether survivin immunoreactivity in STUMP and LMS may play a role in determining recurrence.Material and Methods: Consecutive 119 specimens of leiomyoma, leiomyoma variants, STUMP and LMS from the pathology archives of Bezmialem Medical Faculty and Cerrahpasa Medical Faculty were selected. Clinicopathologic characteristics were analyzed and specimens were stained with survivin and Ki-67. The percentage and staining intensity of immunoreactive cells were examined. Additionally, we analyzed whether survivin intensity and expression might be a predictor of LMS recurrence.Results: The patients in the LMS group were older (p 0.001). All LMS and all STUMP specimens were stained with survivin. Survivin staining and Ki-67 staining were highest in the LMS and STUMP groups. Survivin staining was 14.2 ± 6.7 % in the LMS group, 11.2± 10.4 % in the STUMP group, 1.85 ± 1.9 % in the leiomyoma group and 1.4 ± 0.2 % in the leiomyoma variant group (p0.001). Survivin staining intensity was 1.2 ± 0.6 in the LMS group, 0.9 ± 0.2 in the STUMP group, 0.8 ± 0.4 in the leiomyoma group and 0.9 ± 0.3 in the leiomyoma variant group ( p=0.025). Both survivin staining percentage and staining intensity correlated with the Ki-67 proliferation index. In the LMS cases that showed recurrence survivin staining was 16% while in the cases that did not reoccur survivin staining was 2% (p0.001).Conclusion: The antiapoptotic marker “survivin” has not been studied before for smooth muscle tumors of the uterus. Utilizing survivin in conjuncture with histologic features and Ki-67 can also help to determine malignancy potential and LMS recurrence.